Hubungan Pola Asuh Orang Tua Dengan Kejadian Sibling Rivalry Anak 3-5 Tahun Di PAUD Annora Pelangi Kecamatan Tabalar - Vatika, Yuni; Widyastuti , Wiwin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: To investigate the correlation between the type of parenting style adopted by parents and the incidence of sibling rivalry in children aged 3-5 years. Methods: This research is an observational analytical approach that uses a cross-sectional approach. The population is all families or parents who have more than one child, one of the children is still in the age range of 3-5 years. The total number of families that meet these criteria is 130 families. The number of respondents taken as samples was 42 parents. Results: calculation analysis test results show the Exact Sig value. (2-sided) (p) is 0.000, with p≤ 0.05, and a Contingency coefficient value of 0.651. Conclusion: 1) Authoritarian and democratic parenting tends to be the main choice for most parents in Tubaan Village, Tabalar District, Berau Regency. 2) The majority of children aged 3-5 years in Tubaan Village, Tabalar District, Berau Regency experience sibling rivalry. 3) There is a significant relationship between the type of parenting style applied by parents and the incidence of sibling rivalry when children are 3-5 years old.